Desenvolvimento de um datalogger configurável e de baixo custo para aplicação em pesquisas ambientais - Carneiro, Édipo Alexandre Pereira (2022)
Research involving the evaluation of environmental parameters requires the acquisition of a large mass of data in different intervals and quantities. Such data must be accurate and reliable, and its observation can exceed the limits of human capacity because of the need to record events that happens in a very short or very long time span. To meet this need, the main objective of this work was to develop a data logger that can be used in different research areas, is economically viable and easy to use. To this end, some existing academic and commercial solutions and the technical and methodological aspects used in these designs were first evaluated. Then, concepts of agile software development methodology were applied to create the project and prepare the layers of hardware, firmware and software that make up the data logger. Once the prototype design was completed, a pilot test was conducted to evaluate whether the prototype met all identified requirements. Subsequently, a case study was conducted in which the data logger was used to automate the data acquisition of a rainfall simulator built at the Universidade do Oeste do Paraná (UNIOESTE), campus of Cascavel/ PR, to develop and validate models of water and soil loss by runoff as a function of vegetation cover. For this purpose, nine analog soil moisture sensors, one digital water flow sensor, and one digital ultrasonic sensor were used. The whole process of calibration and data collection of this application is described step by step and the collected data are presented, statistically analyzed and then compared with a commercial data logger to confirm aspects such as the accuracy and stability of the solution. Taking into account all the analyzes performed, it was found that the academic data logger proved to be stable and precise, allowing the data collection to be performed by the researchers involved without any failures or operational difficulties. The total cost of building a data logger was $192.35. Thus, the main goal was achieved: to create a cost-effective and easy to use solution for use in environmental research